The Humor as a Form of Artistic Expression in Education - Eşi Marius Costel (Sciendo, 2021)
The relevance of the idea of humor at the social level expresses, from our viewpoint, the need to understand, assume and, why not, use it at the level of social communities. Under these conditions, we consider the usefulness and functionality/applicability of such an idea in educational terms, and in particular, at the level of the class of students. Such an idea is the very idea of humor as it is found in the educational dimension. Moreover, our interest is focused upon seeing and to what extent, the idea of humor can be considered to be an art, if we consider stylized / "aestheticized", artistic, expressive criteria. That is why, the assumed purpose of this approach that we have achieved consists in an exhaustive analysis of the idea of humor and, implicitly, of the art of humor in education, as well as of the way in which it manifests and it is recognized at the educational level.